Health Behaviours among Travellers Regarding Risk Compensation Following COVID-19 Vaccination in Taizhou, China - Meng-Ge Yang; Li-Jun Wang; Lu-Yin Xu; Mang Ke; Liang-Xue Sun (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. During the COVID-19 pandemic, public transport was restricted in many countries because of the transmission risk. According to the risk compensation theory, travellers post-COVID-19 vaccination may encounter higher risks; however, no real-world studies provide such evidence. Therefore, we conducted a survey to assess whether risk compensation would occur among travellers’ health-related behaviours after COVID-19 vaccination, potentially aggravating the transmission of the virus. Materials and Methods. A self-administered online survey was designed and distributed over WeChat to identify the difference in health behaviours before and after COVID-19 vaccination among travellers at a train station in Taizhou, China, from 13 February to 26 April 2022. Results. A total of 602 individuals completed the questionnaire. The results revealed no statistical difference between the health behaviours reported by the vaccinated and unvaccinated groups. Participants who received the first dose of the vaccine earlier showed no statistical difference in harmful health behaviours (hand washing frequency decreased by 4.1% P=0.145) and the duration of public transport travel increased by 3.4% P=0.437)), but showed better protective health behaviours (mask-wearing duration increased by 24.7% P=0.014)). Compared to those vaccinated less than three times, participants vaccinated against COVID-19 three times showed no statistical differences in harmful health behaviours mask-wearing duration decreased by 7.0% P=0.927), their hand washing frequency decreased by 4.8% P=0.905), and the duration of public transport travel increased by 2.5% P=0.287). After vaccination, when compared to themselves before vaccination, participants exhibited better health behaviours (increased hand washing frequency and mask-wearing duration, and decreased duration of public transport travel) to some extent. Conclusion. In conclusion, this study found no evidence of risk compensation among travellers. After being vaccinated, health behaviours partly improved among travellers.